Anti-infectious activity in plants of the genus Tabebuia - Jiménez-González, Francisco Javier; Grupo Polifenoles. Facultad de Tecnología, Universidad Tecnológica de Pereira, Pereira, Colombia. (2013)
Infectious diseases are a worldwide public health problem. There is growing research in the field of new plant-based drugs for treating such diseases. Our objective was to perform a systematic literature review to evaluate the anti-infectious activity (antibacterial, antifungal, antiviral and antiparasitic) attributed to plants of the Tabebuia (Bignoniaceae) genus. We conducted a search for the period of 2000-2013 in ScienceDirect, Scopus, PubMed, Embase, Napralert and SciELO databases using the following MeSH terms: Tabebuia, biological activity, bioactive compounds, chemical compounds, diseases, traditional medicine, tropical infections, infections and treatment. We found ethnobotanical and experimental (in vitro) evidence supporting the use of Tabebuia species for treating infectious diseases. In addition, the compounds responsible for their antimicrobial activity have been  isolated, and their structures have been elucidated, emphasizing among them naphthoquinones such as lapachol. Natural products isolated from Tabebuia plants may be an alternative for developing new anti-infectious agents.